'Harmful' traditional practices: interventions to address gendered forms of violence against women and girls. (1st March 2011) - Creighton, S; Gill, A
Abstract : Harmful cultural or harmful traditional practices (HTP) have been a concern for the violence against women movement and the health service for a number of years. These forms of violence include female genital mutilation (FGM), prenatal sex selection, child marriage, forced marriage and so-called honour-killings/honour based violence (HBV). They are not individual, isolated cases of violence, but expressions of discriminatory social, cultural and religious norms that define women's subordinate position in the family, community and society and enforce control over women's freedom, including their sexuality. By focussing on the panoply of expressions of HBV, particularly those relating to marriage and FGM practices which unfortunately still impact on many women in the UK. We will draw international attention to the HTP in the name of which women continue to be subjected to violence. To date, most laws enacted to address HTP have consisted of amendments to national criminal laws. These amendments have certainly condemned violence against women, and thereby constitute an important step towards ending the impunity enjoyed by its perpetrators. However, these measures do not provide for victim support or require preventative health measures to be taken. Health professionals in FGM cases, for example, often have first contact with a victim/survivor of a 'harmful practice' only if there has been a medical complication. It is therefore imperative that these professionals are trained to identify violence and sensitively treat its victims/survivors. Citing findings from the recent violence against women and girls (VAWG) Home Office and Department of Health stakeholder events in 2009, we offer recommendations related to these practices and call for more regular and systematic training for health professionals particularly those working in maternity, obstetrics, gynaecology and sexual health in assisting those affected by harmful traditional practices.